Using the novel FLC dynamic buffer size tuning technique to support more dependable location-aware information retrieval. - Lin, W.; Dillon, Tharam S.; Wong, A. (IEEE, 2005)
This paper proposes to use the novel Fuzzy Logic Controller (FLC), which is a dynamic buffer size tuning technique, to support more dependable location-aware information retrieval. Within a smart space supported by mobile/pervasive computing a user may request service from the surrogate through a portable SFF (small-for-factor) device (e.g. PDA). Therefore, the one-surrogate-to-many-SFF-clients relationship or asymmetric rendezvous can easily lead to surrogate reception buffer overflow during peak demand periods. In fact, the traffic of requests to a surrogate is tied in with the transient traveler traffic through the smart space, for example, an airport. Once overflow has happened the user cannot benefit from the cyber foraging supported by the infrastructure. The FLC adaptively tunes the surrogate buffer size so that the buffer length always covers the queue length by the given? safety margin. In this way the chance of surrogate reception buffer overflow is eliminated, and as a result the asymmetric rendezvous becomes more reliable and dependable, leading to shorter SFF-client/surrogate service roundtrip time.